Tbx5 and Osr1 interact to regulate posterior second heart field cell cycle progression for cardiac septation. (August 2015) - Zhou, Lun; Liu, Jielin; Olson, Patrick; Zhang, Ke; Wynne, Joshua; Xie, Linglin
Abstract: Rationale: Mutations of TBX5 cause Holt–Oram syndrome (HOS) in humans, a disease characterized by atrial or occasionally ventricular septal defects in the heart and skeletal abnormalities of the upper extremity. Previous studies have demonstrated that Tbx5 regulates Osr1 expression in the second heart field (SHF) of E9.5 mouse embryos. However, it is unknown whether and how Tbx5 and Osr1 interact in atrial septation. Objective: To determine if and how Tbx5 and Osr1 interact in the posterior SHF for cardiac septation. Methods and Results: In the present study, genetic inducible fate mapping showed that Osr1 -expressing cells contribute to atrial septum progenitors between E8.0 and E11.0. Osr1 expression in the pSHF was dependent on the level of Tbx5 at E8.5 and E9.5 but not E10.5, suggesting that the embryo stage before E10.5 is critical for Tbx5 interacting with Osr1 in atrial septation. Significantly more atrioventricular septal defects (AVSDs) were observed in embryos with compound haploinsufficiency for Tbx5 and Osr1 . Conditional compound haploinsufficiency for Tbx5 and Osr1 resulted in a significant cell proliferation defect in the SHF, which was associated with fewer cells in the G2 and M phases and a decreased level of Cdk6 expression. Remarkably, genetically targeted disruption of Pten expression in atrial septum progenitors rescued AVSDs caused by Tbx5 and Osr1 compound haploinsufficiency. There was a significant decrease in Smo expression, which is a Hedgehog (Hh) signaling pathway modulator, in the pSHF of Osr1 knockout embryos at E9.5, implying a role for Osr1 in regulating Hh signaling. Conclusions: Tbx5 and Osr1 interact to regulate posterior SHF cell cycle progression for cardiac septation. Highlights: Osr1 and Tbx5 interact for cardiac septation. Regulation of Osr1 by Tbx5 in posterior SHF is time-sensitive. Tbx5 and Osr1 interact to regulate the atrial progenitor cell cycle progression. Pten knockdown rescued AVSDs caused by Osr1 and Tbx5 compound haploinsufficiency. Integrity of the Hh signaling was dependent on Osr1 level and is time-sensitive.